Basic Surveillance Parameters Improve the Prediction of Delayed Cerebral Infarction After Aneurysmal Subarachnoid Hemorrhage - Csók, István; Grauvogel, Jürgen; Scheiwe, Christian; Bardutzky, Jürgen; Wehrum, Thomas; Beck, Jürgen; Reinacher, Peter C.; Roelz, Roland (Frontiers in Neurology, 2022)
Background: To establish a practical risk chart for prediction of delayed cerebral infarction (DCI) after aneurysmal subarachnoid hemorrhage (aSAH) using information that is available until day 5 after ictus. Methods: We assessed all consecutive aSAH patients admitted to our service between 09/2008 and 09/2015 (n=417). The data set was randomly split into thirds. Two thirds were used for model DEVELOPMENT, one third for VALIDATION. Characteristics that were present between the bleeding event and day 5 (i.e. prior to >95% of DCI diagnoses) were assessed to predict DCI using logistic regression models. A simple risk chart was established and validated. Results: The amount of cisternal and ventricular blood on admission computed tomography (Hijdra-Score), early sonographic vasospasm (i.e., mean flow velocity of either intracranial artery > 160cm/s until day 5) and a simplified binary level of consciousness score until day 5 were the strongest predictors of DCI. A model combining these predictors delivered a high predictive accuracy (area under the receiver operating characteristic curve (AUC) of 0.82, Nagelkerkes’ R2 0.34 in the DEVELOPMENT cohort). Validation of the model demonstrated a high discriminative capacity with an AUC of 0.82, Nagelkerkes’ R2 0.30 in the VALIDATION cohort. Conclusion: Adding level of consciousness and sonographic vasospasm between admission and post-bleed day 5 to the initial blood amount allows for simple and precise prediction of DCI. The suggested risk chart may prove useful for selection of appropriate candidates for interventions to prevent DCI.